Hashimoto’s Thyroiditis in a Female Adolescent-Case Report - Ivonne, González-Rodríguez Rebeca; Irma, Jiménez-Escobar; Lorena, Hernández-Delgado; Pedro, Gutiérrez-Castrellón; Conde-Lozano,; Adriana., (Archives of Clinical and Medical Case Reports, 2019)
Adolescent Female, 14 years old, who refers constipation, oligomenorrhea and headache; she has dorsal hump, goiter, acanthosis nigricans, geno valgo, dry skin, Body Mass Index (BMI) 38.5 kg / m2 (>97th percentile), body fat 46.9% (electric bioimpedance), waist circumference >90th percentile, blood pressure in normal values for age and sex. Thyroid profile: TSH 203.19 IUI/ml, T4L 0.29 ng/dl, anti thyroperoxidase antibodies (anti TPO) 359.4 IU/ml. Hashimoto’s Thyroiditis was diagnosed by detecting primary hypothyroidism coupled with elevation of anti TPO. Ultrasound of the neck with increased thyroid lobes without calcification or vascularity. Started levothyroxine 100 ug/day, at 2 months of management: weight loss of 5.5 kg, BMI 36.7 kg/m2, remission of symptoms, with improvement in thyroid function tests.